Physiography and tectonic setting of the subglacial lake district between Vostok and Belgica subglacial highlands (Antarctica) - Tabacco IE; Forieri A; Zirizotti A.; CIANFARRA, Paola; SALVINI, Francesco (Geophysical Journal International, 2006)
We present the interpretation of 11 radio echo-sounding (RES) missions carried out over the Vostok–Dome Concordia region during the Italian Antarctic expeditions in the period 1995– 2001. The extension and the density of the radar data in the surveyed area allowed to reconstruct a reliable subglacial morphology and to identify four relevant morphological structures namely: the Aurora trench, the Concordia trench, the Concordia ridge and the South Hills. These structures show evidence compatible with the presence of tectonic features. Morphological considerations indicate their development in Cenozoic time. Hybrid cellular automata (HCA)- based numerical modelling allowed to justify a possible role played by the tectonics of the Aurora and Concordia trench evolution. This was accomplished by matching the bed profiles along opportunely projected sections with the modelled surfaces as derived by the activity of normal faults with variable surfaces within the continental crust. The Vostok–Dome C region is characterized by a large number of subglacial lakes. From the analysis of basal reflected power echo, we identified 14 new lakes and obtained information about their physiography as well as their possible relations with tectonics.We propose a grouping of subglacial lakes on the base of their physiography and geological setting, namely relief lakes, basin lakes and trench lakes. Relief lakes located in the Belgica subglacial highlands and are characterized by sharp and steep symmetric edges, suggesting a maximum water depth of the order of 100 m. Their origin may well relate to localized, positive geothermal flux anomalies. Basin lakes located in the Vincennes subglacial basin and are characterized by wider dimension that allow the development of well-defined, flat ice surface anomalies. Trench lakes characterize the Aurora and Concordia trenches as the possible effect of normal fault activity.